Design and Evaluation of Coronary Artery Stent Geometry Based on Finite Element Analysis - As'ari, Muhammad Suhairi; Ismail, Al Emran (Research Progress in Mechanical and Manufacturing Engineering, 2024)
The implantation of stents in coronary arteries is a common procedure for patients diagnosed with stenosis, a narrowing of the arteries. Numerous studies have reported a significant relationship between the growth of stenosis and the configuration of stent struts. Different stent geometries result in varying peak stress, residual stress, and recoil percentage within the stented coronary artery. This study aims to determine the static structural behaviour near stent strut configurations based on different parameters. To achieve this, three-dimensional models of stents and simplified coronary arteries with balloons were created using computer-aided design (CAD) software. ANSYS was then used to simulate three different stent shapes. A parametric study was conducted to predict stent performance based on the variations in stent strut geometry. The results showed that all stent models calculated the mentioned parameters. The graphs indicated that the D1 stent model, with a particular stent strut shape, exhibited the lowest residual stress of 120.46 MPa. On the other hand, the D2 stent model demonstrated the lowest peak stress of 299.41 MPa. However, considering all the performance indicators, the D1 stent model exhibited the best overall stent performance compared to the others. In conclusion, the D1 stent model demonstrated favourable stent performance by predicting a lower percentage of thrombosis formation and reducing the growth of re-stenosis.